National Policy of France and Russia in 1870-1914: Comparative Analysis - V. V. Kulbashny; E. G. Vartanyan (Научный диалог)
The article is devoted to the comparison of the national policy of France and the Russian Empire in the last third of the 19th - early 20th centuries. It is shown that France was characterized in the national issue by the desire to take revenge on Germany after the defeat in the Franco-Prussian war, the development of political anti-Semitism, the increase in the level of migration from colonial possessions. Attention is paid to the fact that many nationalities lived on the territory of the Russian Empire. Special attention is paid to the fact that in Russia by the end of the 19th century there was a tightening of national policy, which was aimed at the Russification of representatives of national minorities in order to consolidate the population. The authors dwell on the fact that in the course of national policy in the last third of the 19th - early 20th centuries the French government managed to smooth out the contradictions on the national issue, integrating the population and creating conditions for successful actions within the framework of imperialism. It is shown that in the Russian Empire the national issue was not resolved, becoming one of the causes of the revolution of 1905-1907, as well as one of the destabilizing factors during the First World War.